On the credit and exchange rate channels of central bank asset purchases in a monetary union - Matthieu Darracq Pariès; Niki Papadopoulou (European Central Bank (ECB), 2019)
Through the euro area crisis, financial fragmentation across jurisdictions became a prime concern for the single monetary policy. The ECB broadened the scope of its instruments and enacted a series of non-standard measures to engineer an appropriate degree of policy accommodation. The transmission of these measures through the currency union remained highly dependent on the financial structure and conditions prevailing in various regions. This paper explores the country-specific macroeconomic transmission of selected non-standard measures from the ECB using a global DSGE model with a rich financial sector: we extend the six-region multi-country model of Darracq Pariès et al. (2016), introducing credit and exchange rate channels for central bank asset purchases. The portfolio rebalancing frictions are calibrated to match the sovereign yield and exchange rate responses after ECB's Asset Purchase Programme (APP) first announcement. The domestic transmission of the APP through the credit intermediation chain is significant and quite heterogenous across the largest euro area countries. The introduction of global portfolio frictions on euro area government bond holdings by international investors opens up for a larger depreciation of the euro. The interaction between international and domestic channels affect the magnitude and the cross-country distribution of the APP impact.
Keywords: E4; E5; F4; 330; DSGE models; banking; financial regulation; cross-country spillovers; bank lending rates; non-standard measures